Contribution of dihydrocodeine and dihydromorphine to analgesia following dihydrocodeine administration in man: a PK–PD modelling analysis - Webb, James A (Blackwell Science Inc, 2001)
AIMS: It is not clear whether the analgesic effect following dihydrocodeine (DHC) administration is due to either DHC itself or its metabolite, dihydromorphine (DHM). We examined the relative contribution of DHC and DHM to analgesia following DHC administration in a group of healthy volunteers using a PK-PD link modelling approach. METHODS: A single oral dose of DHC (90 mg) was administered to 10 healthy volunteers in a randomised, double-blind, placebo-controlled study. A computerized cold pressor test (CPT) was used to measure analgesia. On each study day, the volunteers performed the CPT before study medication and at 1.25, 2.75, 4.25 and 5.75 h postdose. Blood samples were taken at 0.25 h (predose) and then at half hourly intervals for 5.75 h postdose. PK-PD link modelling was used to describe the relationships between DHC, DHM and analgesic effect. RESULTS: Mean pain AUCs following DHC administration were significantly different to those following placebo administration (P = 0.001). Mean pain AUC changes were 91 score. s(−1) for DHC and −17 score. s(−1) for placebo (95% CI = ± 36.5 for both treatments). The assumption of a simple linear relationship between DHC concentration and effect provided a significantly better fit than the model containing DHM as the active moiety (AIC = 4.431 vs 4.668, respectively). The more complex models did not improve the likelihood of model fits significantly. CONCLUSIONS: The findings suggest that the analgesic effect following DHC ingestion is mainly attributed to the parent drug rather than its DHM metabolite. It can thus be inferred that polymorphic differences in DHC metabolism to DHM have little or no effect on the analgesic affect.